Lyophilized bone marrow cell extract functionally restores irradiation‐injured salivary glands. (26th February 2018) - Su, X; Fang, D; Liu, Y; Ruan, G; Seuntjens, J; Kinsella, JM; Tran, SD
Abstract : Objective: Bone marrow cell extract (BMCE) was previously reported to restore salivary gland hypofunction caused by irradiation injury. Proteins were shown to be the main active factors in BMCE. However, BMCE therapy requires multiple injections and protein denaturation is a concern during BMCE storage. This study aimed to preserve, by lyophilization (freeze‐drying), the bioactive factors in BMCE. Methods: We developed a method to freeze‐dry BMCE and then to analyze its ingredients and functions in vivo. Freeze‐dried (FD) BMCE, freshly prepared BMCE (positive control), or saline (vehicle control) was injected into the tail vein of mice that had received irradiation to damage their salivary glands. Results: Results demonstrated that the presence of angiogenesis‐related factors and cytokines in FD‐BMCE remained comparable to those found in fresh BMCE. Both fresh and FD‐BMCE restored comparably saliva secretion, increased cell proliferation, upregulated regenerative/repair genes, protected salivary acinar cells, parasympathetic nerves, and blood vessels from irradiation‐damaged salivary glands. Conclusion: Lyophilization of BMCE maintained its bioactivity and therapeutic effect on irradiation‐injured salivary glands. The advantages of freeze‐drying BMCE are its storage and transport at ambient temperature.